Strategies to reduce the number of variables and the combinatorial search space of the multistage transmission expansion planning problem - Rahmani, Mohsen [UNESP]; Romero, Ruben [UNESP]; Rider, Marcos J. [UNESP] (My University, 2013)
This paper proposes strategies to reduce the number of variables and the combinatorial search space of the multistage transmission expansion planning problem (TEP). The concept of the binary numeral system (BNS) is used to reduce the number of binary and continuous variables related to the candidate transmission lines and network constraints that are connected with them. The construction phase of greedy randomized adaptive search procedure (GRASP-CP) and additional constraints, obtained from power flow equilibrium in an electric power system are employed for more reduction in search space. The multistage TEP problem is modeled like a mixed binary linear programming problem and solved using a commercial solver with a low computational time. The results of one test system and two real systems are presented in order to show the efficiency of the proposed solution technique. © 1969-2012 IEEE.
Keywords: Binary numeral system; disjunctive model (DM); GRASP-CP; multistage transmission expansion planning; reduced disjunctive model (RDM); Multi-stage transmission expansion; Expansion; Electric power transmission